Smoking, alcohol consumption and human papillomavirus infection as risk factors for oral cavity and oropharyngeal tumors in Serbia – A pilot study - Božić, Ljiljana; Jeremić, Predrag; Dimitrijević, Milovan; Jovanović, Tanja; Knežević, Aleksandra (Vojnosanitetski pregled, 2021)
Background/Aim. The oral cavity and oropharyngeal cancers are among the most common cancers worldwide with the multifactorial etiology. The aim of this study was to determine the major risk factors among patients with oral cavity and oropharyngeal tumors in Serbia. Methods. A total of 63 patients with biopsy proven malignant (33 patients) or benign (30 patients) oral cavity or oropharyngeal lesions were included in this study. The data about gender, age, smoking habits and alcohol consumption were obtained from the routine medical files. The detection and genotyping of human papillomavirus (HPV) was done in paraffin embedded tissue samples using in situ hybridization. Results. Malignant lesions were more frequent in men, smokers and patients who consume alcohol with a statistically significant difference compared to the patients with benign lesions. The prevalence of HPV infection was higher in patients with malignant lesions compared to patients with benign lesions, but without statistically significant difference. High risk genotypes were detected only in patients with malignant lesions of tonsils and base tongue cancer, while low risk types were demonstrated in patients with benign lesions with a highly statistically significant difference. Conclusion. The results point to the significant association of tobacco smoking, alcohol consumption and high risk HPV genotypes as risk factors for oral cavity and oropharyngeal carcinomas in Serbian patients.